Pengaruh Modal Kerja, Return On Asset Dan Return On Equity Terhadap Pertumbuhan Laba - Zefri Maulana; Khairatun Hisan; Azi Wiranda (Jurnal Investasi Islam, 2023)
This study aims to analyze working capital and profitability ratios on PT. Japfa Comfeed Indonesia Tbk, profitability ratios use the Return On Assets (ROA) and Return On Equity (ROE) indicators. This study uses data collected from the IDX website, namely www.idx.co.id. The data obtained is then processed and adjusted to the needs of researchers during the 2012-2021observation period. Calculation techniques and data analysis using multiple linear regression methods to determine whether there is a significant influence between the variables Working Capital, Return On Assets (ROA), and Return On Equity (ROE) on Profit Growth. Based on the results of the study, working capital has a positive effect on profit growth with a value of 2.555. The Return On Assets (ROA) ratio has a positive effect on profit growth with a value of 42.369. The Return On Equity (ROE) ratio has a positive effect on profit growth with a value of 11,478. Simultaneously Working Capital, Return On Assets (ROA), Return On Equity (ROE) simultaneously have a significant effect on profit growth with a sig value of 0.000 <0.05.